What Is the correlation between clinical and radiographic findings in patients with advanced osteoarthritis of the knee? - Innmann, Moritz Maximilian; Lunz, André; Fröhlich, Larissa Maria; Bruckner, Thomas; Merle, Christian; Reiner, Tobias; Schiltenwolf, Marcus (Journal of Clinical Medicine, 2023)
Knee range of motion and patient-reported outcome measures (PROMs) are often used as screening tools to assess the severity of knee osteoarthritis and guide the decision to refer patients to an arthroplasty clinic. However, there is little understanding regarding the correlation between these factors. Thus, the purpose of this study was to determine the correlation between patient-reported clinical function measured with the Oxford Knee Score (OKS), pain assessed using the visual analog scale (VAS), knee range of motion (ROM), and characteristic radiographic features in patients with advanced osteoarthritis of the knee. A prospective analysis of a consecutive series of 138 patients with advanced unilateral osteoarthritis (OA) of the knee was performed. The severity of radiographic OA was classified according to the most commonly used Kellgren and Lawrence classification (K&L). Spearman’s rank correlation analysis and multiple linear regression analysis were performed. The OKS was used as a dependent variable and was adjusted for pain, ROM, and nine standardized radiographic parameters on multiple views of the tibiofemoral and patellofemoral joint. OKS and pain correlated weakly with the K&L grade (r = −0.289; p = 0.001; r = 0.258; p = 0.002). K&L grade and the degree of patellofemoral joint space narrowing were identified as independent factors being associated with a poorer OKS (coefficient −4.528, p = 0.021; coefficient −2.211, p = 0.038). Slightly worse results were identified for OKS and pain in patients with K&L grade 4 osteoarthritis compared to patients with K&L grade 3 osteoarthritis (∆OKS 5.5 points, p < 0.001; ∆VAS 1.7 points, p = 0.003). There was no significant difference for passive range of motion between patients with K&L grade 3 or 4. When counseling patients with advanced knee osteoarthritis who may be eligible for knee arthroplasty, it is essential to give primary consideration to pain levels and self-reported limitations experienced during daily activities. Relying solely on knee ROM and PROMs is not an effective screening method for guiding the decision to refer patients to an arthroplasty clinic.
Gesehen am 11.10.2023